2016
DOI: 10.4212/cjhp.v69i6.1608
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Venous Thromboembolism Risk in Medical Inpatients Using Different Clinical Risk Assessment Models

Abstract: Background: Symptomatic venous thromboembolism (VTE) occurs in about 1% of patients within 3 months after admission to a medical unit. Recent evidence for thromboprophylaxis in an unselected medical inpatient population has suggested only a modest net benefit. Consequently, guidelines recommend careful risk stratification to guide thromboprophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
5
1
2
Order By: Relevance
“…Our finding that 69% of patients were stratified at low VTE risk at initiation of therapy is consistent with both external validation studies and a retrospective application of the IMPROVE VTE RAM, which found 63% to 80% of adult medical patients to be at low risk . Use of other VTE RAMs in large databases of medical patients has also categorized more than 75% patients to be low risk …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our finding that 69% of patients were stratified at low VTE risk at initiation of therapy is consistent with both external validation studies and a retrospective application of the IMPROVE VTE RAM, which found 63% to 80% of adult medical patients to be at low risk . Use of other VTE RAMs in large databases of medical patients has also categorized more than 75% patients to be low risk …”
Section: Discussionsupporting
confidence: 86%
“…Other RAMs were derived from populations with high percentages of surgical or cancer patients, considered only risk factors present at admission, or in the case of the Padua Prediction model, were empirically generated from a small, single‐centre cohort and found to be poorly predictive of VTE in an external validation model . Moreover, in identifying medical patients at sufficient risk for VTE prophylaxis, the IMPROVE VTE RAM was found to be more restrictive versus the Padua model or an institutional order set designed to meet Canadian accreditation standards in a retrospective chart review . For the assessment of bleed risk, the IMPROVE Bleed RAM remains the only evidence‐derived RAM known to the authors.…”
Section: Introductionmentioning
confidence: 99%
“…8 A Canadian study which used Padua and the IMPROVE predictive risk assessment models, only 21.5% and 7.0% of the patients, respectively, were eligible for thromboprophylaxis at the time of admission. 13 The ACCP guidelines recommends anticoagulant thromboprophylaxis for acutely ill hospitalized medical patients at increased risk of thrombosis. For acutely ill hospitalized medical patients at increased risk of thrombosis who are bleeding or are at high risk for major bleeding, it suggests mechanical thromboprophylaxis with graduated compression stockings or intermittent pneumatic compression.…”
Section: Discussionmentioning
confidence: 99%
“…Respecto al uso desmesurado de tromboprofilaxis en pacientes que no lo necesitaban, un estudio retrospectivo de 298 pacientes encontró que el 21,5% tenía indicación de tromboprofilaxis según escala PADUA, entendiendose que alrededor del 80% no lo requería [2] , proporción cercana a la nuestra en donde aproximadamente el 60% de los pacientes en quienes se administró tromboprofilaxis farmacológica carecían de indicación. Un estudio colombiano que incluyó a 102 pacientes reportó que no había indicación de tromboprofilaxis en un 38,2% de los pacientes a los que se les prescribió, y que de este total, la causa más frecuente de error fue la aplicación a pacientes con bajo riesgo (46,1%) de VTE [24] .…”
Section: Discussionunclassified
“…La condición de tromboembolia venosa (VTE, del inglés venous thromboembolism), que comprende a la trombosis venosa profunda (TVP) y la embolia pulmonar (TEP), es la tercera causa de enfermedad cardiovascular después del infarto agudo de miocardio (IAM) y el accidente cerebrovascular (ACV); además, continua siendo una patología con alta carga de morbimortalidad en pacientes hospitalizados [1][2][3] .…”
Section: Introductionunclassified